Verifikasi Metode Uji Penetapan Logam Terlarut Mangan pada Air Menggunakan Inductively Coupled Plasma Mass Spectrometer - Salimi, Sonny; Wahyuni, Sri; Pratama, Intan; Purnamasari, Erianti Siska (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2025)
Clean water is defined as water used for daily needs that meets the quality standards set by regulations. To qualify as clean water, it must undergo physical and chemical testing, including metal content analysis. One such metal is manganese, which is regulated with a maximum allowable concentration of 100 µg/L due to its potential to cause chronic toxicity at high levels. This study aimed to determine the concentration of dissolved manganese in clean water samples using the Inductively Coupled Plasma Mass Spectrometry (ICP-MS) method at LPKL Perumda Tirtawening. Method verification was conducted to ensure the reliability and accuracy of the analysis. The results demonstrated excellent linearity (r ≥ 0.995), a detection limit below 100 µg/L, precision with %RSD < 0.5 CV Horwitz, and accuracy with a %recovery of 102.03%. These findings confirm that the ICP-MS method is valid and suitable for manganese testing in clean water at LPKL Perumda Tirtawening.